Assessment of biomechanical properties of specially-designed miniplate patterns in a mandibular subcondylar fracture model with finite element analysis and a servohydraulic testing unit - ATALI, ONUR (CHURCHILL LIVINGSTONE, 2020)
The aim of our study was to compare the biomechanical stability of three different systems used to fix mandibular condylar fractures on synthetic polyurethane mandibles using a servohydraulic testing unit and finite element analysis (FEA). We measured the resistance to displacement loads causing 1.75 and 3.5 mm displacements of the fragments, and the maximum resistance values before failure of the fixation system in 30 condylar necks of 15 polyurethane mandible models. The three subgroups investigated were arranged as a triangular plate (n = 10), a quadrangular plate (n = 10), and a straight miniplate (n = 10). The most successful fixation pattern was achieved with two straight four-hole miniplates. However, the triangular plate can easily be applied as a second option by an endoscopic approach. The rectangular plates showed no success in mandibular condylar fractures. (C) 2020 The British Association of Oral and Maxillofacial Surgeons. Published by Elsevier Ltd. All rights reserved.
Keywords: biomechanics; finite element analysis; mandibular condyle; surgical fixation; CONDYLAR HEAD FRACTURES; SPLIT RAMUS OSTEOTOMY; INTERNAL-FIXATION; MECHANICAL CHARACTERISTICS; PLATING TECHNIQUES; ANGLE FRACTURES; OSTEOSYNTHESIS; MANAGEMENT; SYSTEMS; 3D